Real Estate Investor's Checklist - Irwin Robert (MC Graw Hill, 2005)
Whether you're just starting out or have years of investing experience, Real Estate Investor's Checklist is the perfect tool for making sure you don't miss out on great opportunities or skip vital steps in the investing process.